Pengaruh Budaya Organisasi terhadap Motivasi Kerja Pegawai BPSDM Provinsi Jambi - Sutoro Sutoro (Universitas Batanghari Jambi, 2020)
The purpose of this study was to determine the description of organizational culture and work motivation, and to determine the effect of organizational culture on employee work motivation at the Human Resources Development Agency (BPSDM) of Jambi Province. This research uses descriptive quantitative method with data collection methods using questionnaires to 75 respondents. The result is that organizational culture has a positive and significant effect on employee motivation at 20.16. The conclusion is that organizational culture influences work motivation in BPSDM Jambi Province by 20.16%.